Business intelligence cookbook : a project lifecycle approach using Oracle technology : over 80 quick and advanced recipes that focus on real-world techniques and solutions to manage, design, and build data warehouse and business intelligence projects /: a project lifecycle approach using Oracle technology : over 80 quick and advanced recipes that focus on real-world techniques and solutions to manage, design, and build data warehouse and business intelligence projects. (2012) - (Computer scientist), Heaton, John
No abstract available